Evaluation of miscible CO2-flooding to improve oil recovery in a clastic heterogeneous reservoir - Al-Khazraji, A.K. (Society of Petroleum Engineers, 2016)
Carbon dioxide flooding is considered one of the most commonly used miscible gas injection to improve oil recovery and its applicability has grown significantly due to its availability, greenhouse effect and easy achievement of miscibility relative to other gasses. Therefore, miscible CO2-injection is considered one of the most feasible methods worldwide. For long term strategies in Iraq and the Middle East, most oil fields will need to improve oil recovery as oil reserves are falling. This paper presents a study of the effect of various miscible CO2-injection scenarios on the performance of the highly heterogeneous clastic reservoir in Iraq. An integrated field-scale reservoir simulation model of miscible CO2-flooding is accomplished. The compositional simulator, Eclipse-300 has been used to investigate the feasibility of miscible CO2-injection process. The process of the continuous CO2-injection was optimized to start in January 2056 as an improved oil recovery method after natural depletion and water flooding processes have been performed, and it will continue until January 2063. The minimum miscibility pressure (MMP) for CO2 was determined using empirical correlation as a function of crude oil composition and its properties. Ten miscible CO2-injection options were undertaken to investigate the reservoir performance. These options included applying a wide range of the CO2-injection rates ranged between 1.25 to 50 MMScf/day. All development options were analyzed with respect to net present value (NPV) calculations to confirm the more feasible CO2development strategy. The results showed that the application of CO2-injection option of a 20 MScf/day attained the highest recovery of 28 by January 2063 among the others. The recovery growth was so minor by the increasing the CO2-injection rate above this level. Based on economic findings the option of 20 MScf/day also attained the highest net present value (NPV). The results showed that after January 2063, the oil recovery attained by the different CO2-injection options are less than the one attained by the waterflooding process. Therefore, the miscible CO2-injection became unviable economically after January 2063. Copyright 2016, IADC/SPE Asia Pacific Drilling Technology Conference.